An FDA-Drug Library Screen for Compounds with Bioactivities against Meticillin-Resistant Staphylococcus aureus (MRSA) - Qiu Ying Lau; Yoke Yan Fion Tan; Vanessa Chai Yin Goh; David Jing Qin Lee; Fui Mee Ng; Esther H. Q. Ong; Jeffrey Hill; Cheng San Brian Chia (MDPI AG, 2015)
The lack of new antibacterial drugs entering the market and their misuse have resulted in the emergence of drug-resistant bacteria, posing a major health crisis worldwide. In particular, meticillin-resistant Staphylococcus aureus (MRSA), a pathogen responsible for numerous human infections, has become endemic in hospitals worldwide. Drug repurposing, the finding of new therapeutic indications for approved drugs, is deemed a plausible solution to accelerate drug discovery and development in this area. Towards this end, we screened 1163 drugs approved by the Food and Drug Administration (FDA) for bioactivities against MRSA in a 10 μM single-point assay. After excluding known antibiotics and antiseptics, six compounds were identified and their MICs were determined against a panel of clinical MRSA strains. A toxicity assay using human keratinocytes was also conducted to gauge their potential for repurposing as topical agents for treating MRSA skin infections.